Rethinking Public And Private Space in Residential Areas: Potentials for Environmentally Friendly GenderSensitive Housing Strategies - Küçükyazıcı, Ufuk (My University, 2020)
The spatial meaning of the place changes in terms of urban functions and public-private use according to differences in daily life habits. Even though everyday life activities have an ordinary feature and are interpreted as invisible in urban design, individual lifestyle habits have an impact on the built environment. Therefore, there is a reciprocal interaction between user (individual), space (the built environment), and community (social structure). Residential areas have a unique environment to examine the changes in spatial characteristics of everyday life activities because these areas accommodate both private and public sphere use. Although architecture and planning define public space and private space use as if they were two separate issues, social structures and spatial configurations mean that there are intermediate spatial characteristic between public and private space in residential areas. In this report, public and private space use hierarchy in residential areas is examined from a feminist perspective in terms of daily life habits for developing sustainable housing areas.
Keywords: Everyday Life Activities; Public and Private Space; Feminist Perspective in Architecture; Gündelik Yaşam Etkinlikleri; Kamusal ve Özel Alan; Mimarlıkta Feminist Perspektif